Hubungan Karakter Religious terhadap hasil belajar peserta didik pada muatan pelajaran agama islam - Puji Utami; Juwita Saputri; Roy Andre Ferdinan; Naufal Aqila Kusnadi (Journal Evaluation in Education (JEE), 2022)
Research objectives: This study aims to determine the relationship between the character of social care and the learning outcomes of students in class V, theme 4, sub-theme 1 of learning 3, "My Blood Circulation is Healthy." Methodology: This research is a quantitative study. The sample in this study was 12 fifth-grade students at SD Negeri Sungai Jernih, with the sampling technique being random sampling. The data collection instrument used was a social care character questionnaire. The data obtained were then analyzed using descriptive statistics and inferential statistics. Main Findings: The results obtained are that there is a relationship between the social care character and the learning outcomes of students with a sig. 0.00 < 0.05. This shows that the character of social care has a significant relationship with learning outcomes Novelty/Originality of this study: This study shows a relationship between socially caring characters and student learning outcomes in the subject matter of Theme 4, sub-theme 1 of learning.